Review on Recent Applications of Cold Plasma for Safe and Sustainable Food Production: Principles, Implementation, and Application Limits - Mohamed Majdi Cherif; Imen Assadi; Lotfi Khezami; Naoufel Ben Hamadi; Aymen Amine Assadi; Walid Elfalleh (Applied Sciences, 2023)
The food and agricultural industries have numerous practical advantages to be gained from the use of cold plasma technology. This paper attempts to showcase the possible uses of cold plasma in the food sector, while also highlighting the most recent developments and market trends. The efficiency of cold plasma in enhancing food products’ quality and shelf life has been demonstrated in several investigations. This review has concentrated on current research into how this technology affects various food chain production stages. Cold plasma has become a cutting-edge non-thermal technique that can be used to ensure food safety. The precise mechanism underlying the effectiveness of cold plasma is still unclear. Understanding these mechanisms and potential elements that can restrict or increase their effectiveness and results is crucial to further enhancing and implementing cold plasma treatment in food processing. The main objective of this review is to investigate the use of plasma, its exceptional characteristics, and its advantages in safe, sustainable food production. In particular, this review summarizes recent studies on the use of cold plasma for microorganisms and pesticides treatment, compiling them and discussing their content. As reported in the literature, a critical point has also been reviewed about some diverse plasma configurations. A comparative study of the efficacy of cold plasma in environmental applications (microorganisms/pesticides) has also been reviewed from the literature.